THE ENSURING SECURITY OF DIPLOMATIC COMPLEXES BY ARCHITECTURAL PLANNING DECISIONS - A D Razin (RUDN Journal of Engineering Research, 2015)
The article considers the problem of ensuring the security of diplomatic complexes consisting of different types of buildings, it depends of number of storeys and functional purpose. The basic security: architectural technical and organizational. Architectural and planning experience and normative documents on fire safety were analyzed. It was proposed solutions to the security of the diplomatic complexes